IMPLEMENTASI KERJASAMA UNICEF DAN INDONESIA DALAM STRATEGI NASIONAL PENANGANAN ANAK TIDAK SEKOLAH (STRANAS ATS) (STUDI KASUS: NAGARI TARUANG-TARUANG TAHUN 2020-2021) - Atikha Sari; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study analyzes the implementation of cooperation between UNICEF and Indonesia in the National Strategy for Handling Out of School Children (STRANAS ATS). The case study taken is the Implementation of Sranas ATS by Nagari Taruang-Taruang as a pilot project for a Community-Based Development Information System (SIPBM). Based on SUSENAS data for 2019 there are 4.3 million school-age children who are not in school. In Nagari Taruang-Taruang there are children who are out of school with various categories and causes, where the main causes are economic factors and a lack of public awareness of the importance of education, so that Nagari Taruang-Taruang receives attention from the government for the education problems that occur. This study uses qualitative methods with primary data collection techniques by conducting interviews. The perspective used is constructivism and uses the Theory of Public Policy and International Cooperation. The level analysis used is the group level. The results of this study indicate that Nagari Taruang-Taruang carried out various stages and programs in implementing the ATS National Strategy. Nagari Taruang-Taruang helps non-school children to resume their education. In addition, Nagari Taruang-Taruang also seeks to restore motivation to study and school for children at risk of dropping out (ABPS) by carrying out the Back-to-School Movement. Nagari Taurang-Taruang also won an award as an Education Care Village from UNICEF and the Ministry of Village PDTT in efforts to handle ATS and ABPS. Keywords: Program Implementation, Stranas Ats, UNICEF, SIPBM